KOMPETENSI GURU DALAM IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN AKIDAH AKHLAK DALAM MENINGKATKAN SIKAP SPIRITUAL SOSIAL PESERTA DIDIK KELAS IV MIN 11 KOTA BANDAR LAMPUNG - NIZA NUR AZIZAH; AHMAD RIFA’I ABUN; MUJIATUN (UNISAN JURNAL, 2025)
Spiritual education should be attached and integrated in every curriculum that applies in the country. Should all management and education providers animate spiritual education as an endeavor for answers in the midst of bad and corrupt morality and only with spiritual education is moral damage and various national problems can be overcome properly. The results of this study are as follows: first, set an example, play motivational videos, and always remind students to always do good; secondly, the driving factor, the subjects of morality are directly related to the spiritual, then the school rules are directly related to the spiritual, and the number of subjects of religion; third, inhibiting factors, the influence of the external environment on the development of children and mosque facilities outside the school; fourth, approach to students who have problems, and find out things that are violent